Study of varieties and processing methods on the quality of arabica coffee beans (Coffea arabica L.) - Zicran Zicran; Rita Hayati; Siti Hafsah (Agrium, 2026)
This study investigated the effects of coffee variety and postharvest processing methods on the quality of Gayo Arabica coffee. The research was conducted at the Horticulture Laboratory and the Seed Technology Laboratory, Faculty of Agriculture, Syiah Kuala University, from December 2025 to January 2026. A factorial randomized block design with a 3 × 3 arrangement and three replications was used. The first factor comprised three Gayo Arabica varieties (Gayo 1; Gayo 2, and Gayo 3), and the second factor comprised three processing methods: wet, dry, and honey. Observed parameters included weight loss, moisture content, pH, caffeine content, color (L, a, b), and organoleptic properties (color, texture, aroma, and overall acceptance). Data were analyzed by ANOVA followed by the least significant difference test at the 5% significance level. Results showed that coffee variety significantly affected weight loss, moisture content, color a and b, and sensory texture, aroma, and overall acceptance; variety had a highly significant effect on caffeine content. Processing method significantly influenced weight loss, moisture content, and color b, and had a highly significant effect on caffeine content, but had no significant effect on pH or most sensory attributes. Dry processing produced the greatest weight loss, while the honey process resulted in the lowest weight loss and the highest caffeine content. All treatments met the Indonesian National Standard for moisture content. Gayo 3 exhibited the best sensory quality, particularly in aroma and overall acceptance.